2010
DOI: 10.1002/ijc.25036
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress‐dependent increase in ICAM‐1 expression promotes adhesion of colorectal and pancreatic cancers to the senescent peritoneal mesothelium

Abstract: Intercellular adhesion molecule-1 (ICAM-1) has been implicated in adhesion of colorectal and pancreatic cancer cells (of the SW480 and PSN-1 line, respectively) to the peritoneal mesothelium. It has been demonstrated that ICAM-1 expression increases with senescence in some cell types, however, the significance of this phenomenon in the context of malignant dissemination remains elusive. In this report we show that the adherence of SW480 and PSN-1 cells to senescent human omentum-derived mesothelial cells (HOMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 63 publications
6
44
0
Order By: Relevance
“…ICAM-1 expression is stimulated in tumour cells by various oncogenic stimuli via NFjB and AP-1 transcription factors, leading to an enhanced cell motility (Ahmed and Kundu 2010;Yang et al 2010) and invasive potential (Rosette et al 2005). In addition, ICAM-1 is expressed in endothelial cells which is corroborated by our immunohistochemical results (Fox et al 1995;Ksiazek et al 2010). Binding of ICAM-1 positive tumour cells to endothelial layers is facilitated by interaction with ß2 integrin-positive neutrophils after stimulation with chemokines, leading to enhanced metastasis in nude mice (Dong and Robertson 2009;Strell et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…ICAM-1 expression is stimulated in tumour cells by various oncogenic stimuli via NFjB and AP-1 transcription factors, leading to an enhanced cell motility (Ahmed and Kundu 2010;Yang et al 2010) and invasive potential (Rosette et al 2005). In addition, ICAM-1 is expressed in endothelial cells which is corroborated by our immunohistochemical results (Fox et al 1995;Ksiazek et al 2010). Binding of ICAM-1 positive tumour cells to endothelial layers is facilitated by interaction with ß2 integrin-positive neutrophils after stimulation with chemokines, leading to enhanced metastasis in nude mice (Dong and Robertson 2009;Strell et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…One of these pathologies is ovarian malignancy, which most frequently metastasizes into the peritoneum, in particular the omentum, and whose incidence and degree of invasiveness rise exponentially with age. Because senescent HPMCs have been found to promote cancer cell adhesion (Ksiazek et al 2009a; Ksiazek et al 2010) and create a pro-angiogenic environment (Ksiazek et al 2008a), their presence in the peritoneum in vivo strongly strengthens the possibility of their causative involvement in age-related exacerbation of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Ksiąźek's group has shown that senescent omentum-derived human peritoneal mesothelial cells (HPMCs) stimulate proliferation, migration and invasion of colorectal and pancreatic cancers in vitro and in vivo creating a metastatic niche for peritoneal spread. These senescent HPMCs facilitate their peritoneal adhesion via the expression of cell-bound ICAM-1 [48, 49]. Recently they have also shown that under certain conditions HPMCs are capable of inhibiting growth of colorectal and pancreatic cancers in a mechanism involving the anti-adhesive capabilities of soluble ICAM-1 [50]".…”
Section: Discussionmentioning
confidence: 99%